Improving the Quality of Literacy Through a Participative Approach in Teaching and Learning in Sambik Bangkol Village - Bintara, Lafaz Yoga; Nurjannah, Nurjannah; Kusuma, Ilham Wirahadi; Martin, Tarisya; Hotimah, Husnul (Abdi Masyarakat, 2024)
Community Service Activities carried out by KKN STKIP Hamzar students in Klongkong Hamlet, Sambik Bangkol Village, aim to increase literacy among the local community. The low ability to read and write among children and teenagers in this hamlet is a major concern. This literacy program includes the establishment of village libraries, the implementation of reading and writing classes, and training for local volunteer teachers. The approach used is participatory, actively involving the community in every stage of program implementation. The results of this activity showed a significant increase in the participants' interest in reading and literacy skills, as well as an increase in public awareness of the importance of education. It is hoped that this program can become an example for similar initiatives in other regions with the same challenges.